(3CSQGQ GdJQhjL aj YUQ GdYhdeI (B:s (3JLGQH TQcGJ OhdjI aj GdJQhjL (B/s - (3YHO GdUHhQ, eMSf aJMjs ((3GdbGgQI (B:s (3eLehYI Gdfjd GdYQHjI ,s, 2001)
- (3jJfGhd QDjI eSJbHdjI ddJQhjL aj GdbQf GdhGMO h GdYTQjf(B- (3jYQV GdcJGH GSGdjH GdJQhjL HefgL LOjO edGFe GdJShjb aj YUQ GdYhdeI (B- (3jJfGhd GdcJGH GdGSGdjH GdMOjKI ddJQhjL aj YUQ JcfhdhLjG GdeYdheGJ eY GdJQcjR Ydi ehVhY GdJQhjL YjQ THcI GdEfJQfJ (B- (3GdcJGH jYQV dJLGQH MbjbjI dTQcGJ OhdjI aj eLGd GdJQhjL (B- (3jMJhj GdcJGH Ydi aUd NGU Yf GSQGQ fLGM GdjGHGfjjf aj GdJQhjLs
(3HHdjhZQGajG (B: (3U(B.167-168s
Keywords: (3GdEYdGfs; (3GdOYGjIs; (3GdJQhjLs